ANALISIS MASLAHAH PADA FATWA MUI TENTANG AKAD TABARRU’ ASURANSI SYARIAH - Syamsul Bahri (Institut Agama Islam Negeri (IAIN) Bone, 2021)
The concept of giving benefit to life sometimes leads to debate, Differences in determining patterns, criteria, and priorities maslahat not infrequently gave birth to a mafsadat in the form of conflict between fellow Muslims. The absence of limits on the use of maslahat, Majelis Ulama Indonesia (MUI) as a recognized and agreed upon institution in Indonesia to carry out the tasks and issue fatwas in demand to take an active role in seeing the development of human life. Majelis Ulama Indonesia (MUI) is expected to always give a fatwa about the phenomenon of events that developed in the community, so as not to become a bias that will lead to disputes among Muslims. Departing from the background of the authors are interested to discuss the principle maslahat one of the MUI fatwa on tabarru 'funds on the contract of takaful insurance.The method of collecting material in this journal is done by library research. which means done by tracing the legal materials related to the subject matter that is related to akad tabarru 'in the provisions of DSN MUI Fatwa No.21 / DSN-MUI / X / 2001 on General Guidelines for Sharia Insurance, as well as the fatwa DNS MUI No. 53 / DSN- MUI / III / 2006 concerning akar tabarru 'on Takaful Insurance.The results of the analysis show that the concept of maslahat dana tabarru 'on Takaful insurance can be seen on the principle of help please, mutually alleviate the burden of human beings in akar tabarru 'as a form of grant funds to be used for customers. one of the elements is mutual guard and foster brotherhood. Muslims in particular, as servants of Allah swt are required to utilize resources (nature, property, etc.). who has been entrusted by God to him to realize the maximum benefit possible.